A pathogenic variant in the FLCN gene presenting with pure dementia: is autophagy at the intersection between neurodegeneration and cancer? - Bottillo, Irene; Laino, Luigi; Azzarà, Alessia; Lintas, Carla; Cassano, Ilaria; Di Lazzaro, Vincenzo; Ursini, Francesca; Motolese, Francesco; Bargiacchi, Simone; Formicola, Daniela; Grammatico, Paola; Gurrieri, Fiorella (Frontiers in Neuroscience, 2024)
by FLCN gene, plays a role in the mTORC1 autophagy cascade and its alterations are responsible for the Birt-Hogg-Dubé (BHD) syndrome, characterized by follicle hamartomas, kidney tumors and pneumothorax. PATIENT AND RESULTS. We report a 74-years-old woman diagnosed with dementia and carrying a FLCN alteration in absence of any sign of BHD. She also carried an alteration of MAT1A gene, which is also implicated in the regulation of mTORC1. DISCUSSION. The MAT1A variant could have prevented the development of a FLCN-related oncological phenotype. Conversely, our patient presented with dementia that, to date, has yet to be documented in BHD. Folliculin belongs to the DENN family proteins, which includes C9orf72 whose alteration has been associated to neurodegeneration. The Folliculin perturbation could affect the C9orf72 activity and our patient could represent the first human model of a relationship between FLCN and C9orf72 across the path of autophagy.